Differential nuclear ATRX expression in sarcomas - Kölsche, Christian; Renner, Marcus; Johann, Pascal-David; Leiss, Irina; Sahm, Felix; Schimmack, Simon; Wardelmann, Eva; Renker, Eva Kristin; Schirmacher, Peter; Korshunov, Andrey; Deimling, Andreas von; Mechtersheimer, Gunhild (Histopathology, 2016)
Aim Nuclear α-thalassemia/mental retardation X-linked (ATRX) loss and alternative lengthening of telomeres (ALT) are linked in distinct malignancies. We therefore aimed to determine the nuclear ATRX expression correlated with ALT in a comprehensive series of sarcomas. Methods and results A total of 573 formalin-fixed paraffin-embedded sarcomas comprising 28 entities were investigated for nuclear ATRX expression by immunohistochemistry. Telomere-specific fluorescence in-situ hybridization (FISH) was used to determine the ALT phenotype in 50 sarcomas with complete or heterogeneous ATRX loss. Complete nuclear ATRX loss was detected in 58 of 573 sarcomas, all high-grade, with the highest prevalence in undifferentiated pleomorphic sarcomas (38%) and pleomorphic liposarcomas (38%), followed by dedifferentiated liposarcomas (24%), osteosarcomas (21%), leiomyosarcomas (17%), myxofibrosarcomas (11%) and malignant peripheral nerve sheath tumours (4%). Interestingly, a further 20 sarcomas, all belonging to the aforementioned entities with complete ATRX loss, presented with a heterogeneous ATRX expression pattern. ALT was observed in 41 of 42 sarcomas with complete ATRX loss, but only in two of eight sarcomas with heterogeneous expression. Conclusion Nuclear ATRX loss, either complete or heterogeneous, is encountered in a considerable number of high-grade sarcomas with non-specific genetic alterations. A causal relationship with ALT might be indicated at least in cases with a complete nuclear ATRX loss.